Prebiotic Galacto-Oligosaccharide and Xylo-Oligosaccharide Feeds in Pig Production: Microbiota Manipulation, Pathogen Suppression, Gut Architecture and Immunomodulatory Effects - Adam Lee; James S. Stanley; Kenneth H. Mellits; Ian F. Connerton (Applied Microbiology)
Gastrointestinal health is critical to the productivity and welfare of pigs. The transition from milk to plant-based feeds represents an intestinal challenge at wean that can result in dysbiosis and pathogen susceptibility. Prebiotic galacto-oligosaccharides (GOS) and xylo-oligosaccharides (XOS) are non-digestible carbohydrates that can reach the hind gut to promote gut health, either by enhancing the abundance of beneficial members of the intestinal microbiota or via direct interaction with the gut epithelium. Amongst the changes in the intestinal microbiota, GOS and XOS promote populations of short-chain fatty acid (SCFA)-producing bacteria of the genera Lactobacillus, Bifidobacterium and Streptococcus. SCFAs benefit the host by providing nutritional support for the gut, enhance intestinal barrier function and regulate inflammatory responses. By modifying the indigenous microbiota, prebiotics offer a sustainable alternative to the use of antimicrobial growth promoters that have led to the dissemination of antimicrobial resistance and represent a growing threat to public health. This review examines microbial and cellular mechanisms whereby prebiotic feed supplements can support the development of a diverse and robust microbiota associated with a healthy and productive digestive system over the lifetime of the animal, and which is in sharp contrast to the development of dysbiosis often associated with existing antimicrobial treatments. The application of prebiotic feed supplements should be tailored to their modes of action and the developmental challenges in production, such as the provision of GOS to late gestational sows, GOS and XOS to pre-weaning piglets and GOS and XOS to growing/fattening pigs.